Entrepreneurial orientation and open innovation promote the performance of services smes: The mediating role of cost leadership - Mahendra Kumar Chelliah; Kalisri Logeswaran Aravindan; Saravanan Muthaiyah (Administrative Sciences, 2023)
In the 21st century, small and medium service firms face difficulty sustaining their performance. Additionally, the literature on entrepreneurial orientation (EO) in SMEs is scarce. Moreover, the role of cost leadership strategy as a mediator lacks researchers' attention. Therefore, this research aims to examine the relationship between EO and SMEs performance with the mediating role of cost leadership strategy. Based on the contingency theory, a theoretical model has been drawn. A survey approach with a questionnaire technique has been adapted to achieve the study objectives. The data were collected from 283 service SMEs in three states of Malaysia. The Partial Least Square Structural Equation Modelling (PLS-SEM) technique was employed to analyze the empirical data. The study findings highlight that risk-taking and open innovation have no direct relationship with SMEs' performance. However, through the mediation role of cost leadership, risk-taking and open innovation have a significant association with performance. Furthermore, the findings indicate that proactiveness, competitive aggressiveness, and autonomy have a positive and direct relationship with performance, whereas in the presence of cost leadership, competitive aggressiveness has a partial mediating effect. The empirical findings are helpful to policymakers, researchers, and practitioners.
Keywords: 350; cost leadership; entrepreneurial orientation; firm performance; open innovation